Pengaruh Mitra Keagenan, Store Atmosphere, dan Testimoni Terhadap Keputusan Pembelian Produk HNI-HPAI - Siregar Nirma Yunita; Samosir Suhaila Husna; Wulandari Sari; Muhammad Hilman Fikri (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to determine the influence of Agency Partners, Store Atmosphere, and Consumer Testimonials on Purchasing Decisions at the Halal Mart Halal Network International (HNI) Herba Penawar Alwahida Indonesia (HPAI) Store in Melati Village, Pasar 2, Perbaungan. The method used is a quantitative approach with an associative research type. The number of samples is 92 respondents selected using a purposive sampling technique. Data collection was carried out through the distribution of questionnaires with a Likert scale of 1–5. The results of the study indicate that partially, the variables of Agency Partners, Store Atmosphere, and Consumer Testimonials have a positive and significant effect on Purchasing Decisions. Simultaneously, the three variables also have a significant effect with a calculated F value of 44.919 and a significance of <0.001. The coefficient of determination (Adjusted R²) value of 0.591, which means that 59.1% of the variation in Purchasing Decisions can be explained by the three independent variables